Soil hydrology: Recent methodological advances, challenges, and perspectives. Issue 4 (20th April 2015) - Vereecken, H.; Huisman, J. A.; Hendricks Franssen, H. J.; Brüggemann, N.; Bogena, H. R.; Kollet, S.; Javaux, M.; van der Kruk, J.; Vanderborght, J.
Abstract: Technological and methodological progress is essential to improve our understanding of fundamental processes in natural and engineering sciences. In this paper, we will address the potential of new technological and methodological advancements in soil hydrology to move forward our understanding of soil water related processes across a broad range of scales. We will focus on advancements made in quantifying root water uptake processes, subsurface lateral flow, and deep drainage at the field and catchment scale, respectively. We will elaborate on the value of establishing a science‐driven network of hydrological observatories to test fundamental hypotheses, to study organizational principles of soil hydrologic processes at catchment scale, and to provide data for the development and validation of models. Finally, we discuss recent developments in data assimilation methods, which provide new opportunities to better integrate observations and models and to improve predictions of the short‐term evolution of hydrological processes. Key Points: Improved description of small‐scale processes is a key to reduce uncertainty Improve our understanding of hydrology through a network of observatories Data assimilation provides a viable approach to integrate data and models